ANALISIS PENERAPAN AKUNTANSI DANA ZAKAT DAN INFAK/SEDEKAH PADA LEMBAGA AMIL ZAKAT INFAK, DAN SHODAQOH MUHAMMADIYAH (LAZISMU) KABUPATEN MALANG - Rita Anggun Pertiwi; Masiyah Kholmi; Eris Tri Kurniawati (Jurnal Reviu Akuntansi dan Keuangan, 2017)
The purpose of this study is to analyze the application of zakat fund accounting at LAZISMUMalang Regency. Analytical technique is done by using case study research to see the suitabilityof accounting application.the results obtained by this research in general accounting treatmentof zakat by LAZISMU Malang Regency is good enough that includes recognition and distribution. However, measurement, presentation and disclosure are not in accordance with PSAK109.besides, there is no separation between zakat fund and amil fund.Keywords: PSAK 109, zakat fund accounting